2023
DOI: 10.1249/mss.0000000000003144
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Subfield Volumes in Amateur Marathon Runners

Abstract: Purpose: Numerous studies have implicated the involvement of structure and function of the hippocampus in physical exercise, and the larger hippocampal volume is one of the relevant benefits reported in exercise. It remains to be determined how the different subfields of hippocampus respond to physical exercise. Methods: A 3D T1-weighted magnetic resonance imaging was acquired in 73 amateur marathon runners (AMR) and 52 healthy controls (HC) matched with age, sex, and education. The Montreal Cognitive Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Using slightly different segmentation schemes, recent studies including young adults provide further evidence for training-induced volume increases in dentate gyrus/CA3 23 and CA4/dentate gyrus subregions 16 , although preferentially in the left hemisphere. Complementary observations from cross-sectional studies also indicate positive associations of CA4 volume with physical fitness levels 32 . In the rodent hippocampus, physical activity has been shown to preferentially facilitate neurogenesis in the dentate gyrus, and its granule cell and molecular layer more specifically 24 26 , 54 , 68 , 69 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Using slightly different segmentation schemes, recent studies including young adults provide further evidence for training-induced volume increases in dentate gyrus/CA3 23 and CA4/dentate gyrus subregions 16 , although preferentially in the left hemisphere. Complementary observations from cross-sectional studies also indicate positive associations of CA4 volume with physical fitness levels 32 . In the rodent hippocampus, physical activity has been shown to preferentially facilitate neurogenesis in the dentate gyrus, and its granule cell and molecular layer more specifically 24 26 , 54 , 68 , 69 .…”
Section: Discussionmentioning
confidence: 81%
“…Although difficult to measure in vivo, indirect evidence (e.g., for angiogenesis 29 ) suggests that physical activity also promotes neurogenesis in the human hippocampus 30 . While cross-sectional studies observed positive correlations between aerobic fitness level and larger CA1 volumes in male adolescents 31 , and larger volumes for bilateral CA1, CA4, dentate gyrus granule cell and molecular layers, left CA2–3, and the left hippocampal amygdaloid transition area in middle-aged amateur marathon runners 32 , complementary evidence from RCT studies in young adulthood is limited and mixed: In addition to CA4/dentate gyrus volume increases after a 16-weeks training 16 and positive associations between cardiorespiratory fitness improvements and dentate gyrus/CA3 head volume changes after a 12-weeks training 23 , an earlier study also suggested CA2/3, subiculum and dentate gyrus volume decreases after 6-weeks intense aerobic exercise training 18 .…”
Section: Introductionmentioning
confidence: 89%